Pengaruh Gaya Kepemimpinan Otokratis, Beban Kerja dan Stres Kerja terhadap Kinerja Pegawai - Ni Luh Putu Eka Yudi Prastiwi; Suryawan, I Komang Willy (Utiliti Project Solution, 2025)
This study was conducted with the aim of determining the influence of autocratic leadership style in schools, the provision of workload to employees and the level of stress experienced by employees at work which has an impact on the resulting performance. The population and sample of the study were 37 employees. Data collection using the questionnaire method and the analysis technique chosen using SmartPLS 3.0. The results of this study indicate that autocratic leadership style has an impact on increasing employee performance, indicating a positive influence from the original sample of 0.460 and a calculated t value of 4.857> t table 1.96 and significant at 0.000 <0.050. Workload has an impact on increasing employee performance, indicating a positive influence from the original sample of 0.491 and a calculated t value of 4.159> t table 1.96 and significant at 0.000 <0.050. Work stress has an impact on decreasing employee performance, indicating a positive influence from the original sample of 0.333 and a calculated t value of 1.998 > t table 1.96, and a significance of 0.046 < 0.050.